An interview with Samuel Shem, author of 'The House of God'. Issue 4 (4th July 2017) - Brash, Claire
Abstract: Dr Stephen Bergman, Professor of medical humanities at New York University, writes under the name Samuel Shem. He is an acclaimed author of several novels, plays and textbooks, and his work has been translated into several languages –'The House of God' his first novel has sold over 3 million copies. His work exposes the potential moral challenges of the medical workplace and the connection between values, good relationships and healing. In 2015 he visited the UK for medical humanities academic tour which included keynote talks at the RCGP 2015 Annual Conference and at the Royal Society of Medicine. Claire Brash interviewed him at the Royal Society of Medicine.